2018
DOI: 10.1111/jth.14316
|View full text |Cite
|
Sign up to set email alerts
|

The antifibrinolytic and anti‐inflammatory effects of multiple doses of oral tranexamic acid in total knee arthroplasty patients: a randomized controlled trial

Abstract: The antifibrinolytic and anti-inflammatory effects of multiple doses of oral tranexamic acid in total knee arthroplasty patients: a randomized controlled trial. J Thromb Haemost 2018; 16: 2442-53. maximum reductions in blood loss and inflammatory response, improved analgesia, and promoted early rehabilitation. Further studies are required to ensure that these findings are reproducible. A B C D Fig. 4. Postoperative clinical outcomes.Patient-rated pain with 45°knee flexion (A) and at rest (B), knee circumferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 52 publications
0
68
0
Order By: Relevance
“…In one recent study with oral TXA (ref. 3 ), the plasma levels of TXA after oral administration achieved the threshold for the haemostatic effect (10 mg/L) at 10, 14, 18 and 22 h after surgery, and for all of the examined modes (i.e., 1, 2, 3 or 4 doses). A similar arrangement as in our study was also used by Zhang et al, who observed D-dimer and FDP pre-operatively, respectively on the 1 st and 3 rd post-operative day after intravenous, combined and topical administration of TXA.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In one recent study with oral TXA (ref. 3 ), the plasma levels of TXA after oral administration achieved the threshold for the haemostatic effect (10 mg/L) at 10, 14, 18 and 22 h after surgery, and for all of the examined modes (i.e., 1, 2, 3 or 4 doses). A similar arrangement as in our study was also used by Zhang et al, who observed D-dimer and FDP pre-operatively, respectively on the 1 st and 3 rd post-operative day after intravenous, combined and topical administration of TXA.…”
Section: Discussionmentioning
confidence: 85%
“…At higher concentrations, TXA can also directly inhibit plasmin activity 1,2 . It is also believed that TXA has an anti-inflammatory effect (inhibition of plasmin-mediated complement, monocyte and neutrophil inhibition) 3 . Compared with other antifibrinolytics, the effect of TXA is more potentiated by factor X (ref.…”
Section: Introductionmentioning
confidence: 99%
“…In one study of orthopedic surgery patients, intravenous TXA administration both before and after surgery led to increased levels of circulating proinflammatory molecules, such as TNF-α, IL-1β, and IL-6 (38). Conversely, in another cohort of orthopedic surgery patients followed up to 48 h, it was found that an increased number of post-operative oral doses of TXA suppressed IL-6 levels (39). Moreover, prophylactic TXA use in cardiac surgery patients was shown to have an "immune-enhancing" effect, as leukocytes from patients receiving TXA had decreased expression of immunosuppressive surface markers (LAP and PD-L1), and increased expression of immune-activating markers (CD83 and CCR7) (40).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Maniar et al [9] have investigated the serum levels of IL-6 and CRP in the hours and days immediately postoperatively to understand their normal trajectory. However, with the promotion of enhanced recovery after surgery (ERAS), many methods have been used to minimize surgical trauma and reduce inflammation [3,10]. Little is known of the normal curve in the hours and days of CRP and IL-6 immediately postoperatively under an ERAS scenario.…”
Section: Introductionmentioning
confidence: 99%